2017
DOI: 10.14246/irspsd.5.3_53
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Space Layout and Configuration of Shopping Malls in Relation to Pedestrian Movement Behavior - Case of UAE

Abstract: Abstract:The research aims to understand the relationship between the popularity and attractiveness of commercial buildings, shopping malls and any relationship with visitor satisfaction. This would assist in designing new malls or commercial buildings, predict their degree of popularity, and help achieve both higher revenue resulting from increasing the number of visitors and their satisfaction, comfort and enjoyment of the space. This study will focus on the relationship between shopping mall popularity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Kutnicki [9] emphasises that "directing and orientating of shoppers in public mall space is an essential concern for how citizens in a consumer-based economy, not only judge how to move about freely, but also how they situate those judgments according to prearranged forms of spatial guidance systems, such as wayfinding media." Digital signage with wayfinding screens has been proven to enhance shopping mall attractiveness and enjoyment by offering a sense of direction and decrease the time spent getting lost or looking for intended outlets [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Kutnicki [9] emphasises that "directing and orientating of shoppers in public mall space is an essential concern for how citizens in a consumer-based economy, not only judge how to move about freely, but also how they situate those judgments according to prearranged forms of spatial guidance systems, such as wayfinding media." Digital signage with wayfinding screens has been proven to enhance shopping mall attractiveness and enjoyment by offering a sense of direction and decrease the time spent getting lost or looking for intended outlets [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Ten of the reviewed references agreed that Plan Configuration, Architectural Differentiation, and Visual Accessibility are the three most important variables [10]- [12], [18], [19], [23]- [27]. While Garling et al [20] suggested that Plan Configuration and Visual Accessibility are the most effective ones.…”
Section: Weight Of Importance Of Architectural Design Variablesmentioning
confidence: 99%
“…Three references considered Architectural Differentiation as one of the three most affecting variables along with Plan Configuration and Landmarks [2], [14], [15]. In addition to, ten references that regarded it as one of the three most important variables with Plan Configuration and Visual Accessibility [10]- [12], [18], [19], [23]- [27]. Architectural Differentiation was mentioned in seventeen of the reviewed references: thirteen of which considered it one of the three most effective variables.…”
Section: Weight Of Importance Of Architectural Design Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The subject of people's satisfaction and comfort while using spaces takes us to the fourth paper by Meziani and Hussien (2017). Entitled: "A Study On the space layouts and configurations of shopping malls in relation to pedestrian movement behavior-Case of UAE".…”
mentioning
confidence: 99%